ANTARA KARYA FOTO MODEL DARWIS TRIADI DAN JHONNY HENDARTA - Yulianto, Arif (KEMADHA, 2012)
When mentioning Photography  , people will always be attached to  the  name  Derwis  Triadi  .  Andreas  Triadi  Derwis  is  an  icon  of photography in Indonesia . World Photography in Indonesia, we also know  some  professional  photographers  who  dominate  the  field  of commercial and artistic photography Jhonny Hendarta one of them is living in Jogjakarta . They can both draw on the ideas in his mind and forth  in his works  .         The main characteristic picture of the woman who successfully lies in precisely understanding the character , and given light precisely on the photo . Inspiration is key to shooting photography , inspiration distinguishes a work with  the work of others  . Proper shadows will make a photograph has a strong character . Both works show the character on  each  model  ,  the  similarity  between  the  chemistry  and  mood photographer  to  produce  images  with  the  model  properly  .  It  is interesting to Jhonny work that he managed to combine the techniques of photography  , art elements , and elements of the local Indonesian completely on his work  , while  the work of gathering  light Derwis  , artist and model poses on camera  shots  .